Remote Observations of Aeolian Saltation. Issue 16 (16th August 2022) - Cohn, Nicholas; Dickhudt, Patrick; Brodie, Katherine
Abstract: Field measurements of aeolian sediment transport during major storm events are challenging in coastal settings due to the common coincidence of high winds with elevated water levels that can cover beaches. This work demonstrates a new application of lidar to remotely measure properties of wind‐blown sand transport at high spatial resolution. A data set of spatially continuous saltation heights was remotely developed from rapid (7.1 Hz) lidar scanning along a two‐dimensional transect across a beach during wind speeds of between 3.1 and 15.8 m/s associated with the passing of Tropical Storm Isaias. Outputs from the lidar demonstrate the ability to remotely observe the threshold velocity for the initiation of motion for sand transport and show that the upper limit of the saltation layer rises with increasing wind speed. Plain Language Summary: Wind can be an important contributor to landscape changes in sandy desert and coastal environments. There are complex mechanisms by which wind moves sand that are not yet entirely understood. To answer questions about how, when, and why sand is transported by wind, experiments commonly use point‐based sensors that are unable to capture the full spatial and temporal complexity of sand movement very close to the ground. This paper shows that new laser sensors can be utilized to remotely measure properties of sand transport simultaneously at multiple points and with increased detail compared to prior approaches. High resolution, remote measurements from a tropical storm event are used to show how high wind‐blown sand is lifted off of the ground surface and how different wind speeds influence these sand transport patterns. Key Points: Wind‐driven sand transport can be measured using repeat terrestrial laser scanning Remote measurements are used to characterize time and space variable saltation heights during energetic wind forcing Maximum saltation heights respond to changes in wind speed on a coastal beach